ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS DALAM LAPORAN KEUANGAN PT. BANK TABUNGAN NEGARA,Tbk YANG TERDAFTAR DIBURSA EFEK INDONESIA - Putri, Ethika Kirana; Wahadah, Tri Nur; Endarwati, Endarwati; Ayudiati, Citra (Program Studi Manajemen, 2022)
Economic development in a country is highly dependent on the development and real contribution of the banking sector. Financial performance measurement is very necessary in line with the level of banking competition that is increasingly advanced and developing. This study aims to gain an understanding of the condition and health position of bank BTN as one of the companies listed on the Indonesia Stock Exchange. This type of research method uses a descriptive method with a quantitative approach. The data source used is secondary data with analytical techniques using the ratio of Liquidity, Solvency and Profitability. The results of the analysis of the financial statements of the balance sheet, profit and loss and changes in equity using the CR, QR, DR, DER indicators show that the financial performance of Bank BTN in 2018-2021 is declared liquid and solvable, while the ROA and ROE indicators have decreased significantly in 2019. Bank BTN needs to utilize abandoned assets to increase profits and reduce short-term and long-term debt.